Structure–Property Relationships of Dibenzylidenecyclohexanones - Fomina, Marina V; Vatsadze, Sergey Z; Freidzon, Alexandra Ya; Kuz’mina, Lyudmila G; Moiseeva, Anna A; Starostin, Roman O; Nuriev, Vyacheslav N; Gromov, Sergey P (ACS omega, 2022)
A series of symmetrical dibenzylidene derivatives of cyclohexanone were synthesized with the goal of studying the physicochemical properties of cross-conjugated dienones (ketocyanine dyes). The structures of the products were established and studied by X-ray diffraction, NMR spectroscopy, and electronic spectroscopy. All products had the E,E-geometry. The oxidation and reduction potentials of the dienones were determined by cyclic voltammetry. The potentials were shown to depend on the nature, position, and number of substituents in the benzene rings. A linear correlation was found between the difference of the electrochemical oxidation and reduction potentials and the energy of the long-wavelength absorption maximum. This correlation can be employed to analyze the properties of other compounds of this type. The frontier orbital energies and the vertical absorption and emission transitions were calculated using quantum chemistry. The results are in good agreement with experimental redox potentials and spectroscopic data.